Optimum mounting of electronic circuit boards for components and circuits survivability. - Ghazizadeh, Ali. (University of Ottawa (Canada), 1994)
Electronic circuit boards are employed in demanding environments (e.g. satellite, aerospace, marine, automobile, etc.) where the board and mounted components are exposed to vibration of varying amplitude and frequencies. Optimum mounting and component placement to reduce the effect of vibration on the equipment may prolong the service life of the system and reduce costly down time. Electronic boards are often mounted on four rigid support legs. Their vibration is a function of the location of the support legs, and board physical specifications such as length, width, weight, and placement of the components mounted on them. In this study, plate vibration analysis is employed to find the board's free vibration. With the help of nonlinear optimization methods, optimum mounting of circuit boards are investigated. Square board has a better performance than any other board shape. A table of suitable support points will be introduced outlining optimum support points for eight rectangular shapes. For each of these shapes a graph of unsuitable regions is provided to help the designer to avoid placing delicate components over those regions of the plate. Furthermore, the tabulated results can eliminate the need for optimization in non-critical circuit boards or determine a good starting point for optimization. (Abstract shortened by UMI.)
Keywords: Engineering, Electronics and Electrical.